Análise da corrosividade de ligas de cobre em misturas de diesel/biodiesel - Bezerra, Pablo Peterson Lima (Universidade Federal Rural do Semi-Árido, 2018)
Biodiesel is a renewable fuel obtained from vegetable oils or animal fat. This type of fuel is capable of helping to reduce the emission of polluting gases into the atmosphere when added to other fuels, but it is also susceptible to contamination and has impurities that alter its initial properties as fuel, of which, such such as water, microorganisms and trace metals. The corrosion caused by biodiesel is related to the incompatibility of the same with several types of metals and polymers, putting at risk the durability of the automotive motors. Thus, the objective of this work was to evaluate the corrosivity caused by biodiesel content in diesel oil over the copper alloys that are present in many components of the combustion system of the diesel cycle engines. The corrosive effects of copper alloys in diesel / biodiesel mixtures were analyzed by gravimetric and electrochemical linear polarization tests, evaluating mass loss, rate, speed and corrosion resistance. The tests were carried out in the proportions of 10, 15, 20, 25 and 30% of biodiesel in diesel, as the tendency for the next years is for a gradual increase of biodiesel content in diesel. The biodiesel from the residual soybean oil was obtained by transesterification, the diesel oil was purchased at a gas station in the city of Mossoró-RN. Combustion tests, acid index, saponification index and specific mass were performed to characterize the biodiesel. By means of the results obtained in the tests it was possible to observe that the increase of the biodiesel content from the residual oil increases the corrosion rate in the copper alloys, because it has a high acid content and is more hygroscopic than the diesel.
Monografia
Keywords: Corrosão; Ligas de cobre; Biodiesel; Diesel; Ensaio gravimétrico; Polarização potenciodinâmica linear; Corrosion; Copper alloys; Biodiesel; Diesel; Gravimetric assay; Linear potentiodynamic polarization; ENGENHARIAS::ENGENHARIA MECANICA